2014
DOI: 10.3389/fimmu.2014.00376
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into an Old Concept: Role of Immature Erythroid Cells in Immune Pathogenesis of Neonatal Infection

Abstract: Newborns are exceedingly susceptible to infection. However, very little is known about what governs the immunological differences seen in early life that result in extreme vulnerability to infection, nor how this changes during infancy. Herein, I provide evidence that the reduced ability to mount a protective immune response to pathogens is not due to an inherent immaturity of neonatal immune cells but instead the functions of these immune cells are actively suppressed by CD71+ erythroid cells. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 46 publications
3
46
1
1
Order By: Relevance
“…Taken together, these findings contradict the widely held notion that early-primed CD8+ T cells are functionally impaired and unable to produce multiple cytokines at the same levels as adults52. Indeed, our results support the idea that there are no intrinsic defects in the CD8+ T cells early in life, but rather that their activation is strictly regulated by the stimulating microenvironment53, and can be successfully triggered under the appropriate circumstances (see also ref. 54).…”
Section: Discussioncontrasting
confidence: 66%
“…Taken together, these findings contradict the widely held notion that early-primed CD8+ T cells are functionally impaired and unable to produce multiple cytokines at the same levels as adults52. Indeed, our results support the idea that there are no intrinsic defects in the CD8+ T cells early in life, but rather that their activation is strictly regulated by the stimulating microenvironment53, and can be successfully triggered under the appropriate circumstances (see also ref. 54).…”
Section: Discussioncontrasting
confidence: 66%
“…The depletion of human CD71+ cells in cord blood samples unleashes the release of TNF-α and IL-6, as well as the activation of CD8+ T cells 11 . Therefore, umbilical cord CD71+ erythroid cells modulate fetal as well as neonatal immune responses 11, 19 . We found that umbilical cord CD71+ erythroid cells are more abundant in neonates born to women who delivered preterm without labor than in neonates born to women who delivered at term, regardless of the process of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleated erythroid cells express the general erythrocyte marker glycophorin A (or CD235a) [19, 2123] as well as the transferrin receptor CD71, an antigen that is lost upon conversion to mature erythrocytes [24]. Previous studies indicated that CD71+ erythroid cells are partially responsible for immunosuppression of the neonatal immune system [21], and that a reduction in the number and/or functionality of these cells is observed in preterm newborns [25]. A follow-up study claimed, however, that these reticulocytes have a limited role in reducing inflammation driven by microbial colonization [26].…”
Section: Introductionmentioning
confidence: 99%
“…24 Previous studies indicated that CD71+ erythroid cells are partially responsible for immunosuppression of the neonatal immune system, 21 and that a reduction in the number and/or functionality of these cells is observed in preterm newborns. 25 A follow-up study claimed, however, that these reticulocytes have a limited role in reducing inflammation driven by microbial colonization. 26 Recently, we demonstrated that the number and frequency of CD71+ erythroid cells from neonates born to women who underwent spontaneous preterm labor (PTL) are similar to term neonates, but lower than those born to women who delivered preterm in the absence of labor.…”
mentioning
confidence: 99%